Development of Interactive Multimedia Based on Problem-Based Learning to Improve Learning Outcomes of Light Properties Material - Selviana, Selviana; Andriani, Aldina Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The use of technology in science learning media is not optimal, causing low learning outcomes for students. This study aimed to develop a design and test the feasibility and effectiveness of interactive multimedia based on Problem-Based Learning to improve the learning outcomes of fifth-grade students of SDN Pesantren Semarang City. The type of research is Research and Development (R&D) using the Borg and Gall model. The research subjects were 26 fifth-grade students of SDN Pesantren. Data collection techniques using non-test techniques (observation, interviews, questionnaires, and documentation) and test techniques (pre-test and post-test). Data analysis techniques used normality test, t-test, and N-Gain test. The results showed that the design of Problem-Based Learning-based interactive multimedia development using the Canva application contains the main page, main menu, instructions for use, concept map, Problem-Based Learning-based learning materials, virtual laboratories (Dynamic Labs), learning videos, interactive quizzes (Genially), and developer profiles; the feasibility of Problem-Based Learning-based interactive multimedia from material experts 93.75% very feasible criteria and media experts 92.18% very feasible criteria. The results of the teacher response questionnaire are 100% very feasible criteria and 96.80% student response with very feasible criteria; the effectiveness of interactive multimedia based on Problem-Based Learning is shown from the increase in pre-test and post-test scores by 33.65, paired sample t-test results show the significance value (2-tailed) is <0.001 which based on the criteria the value is below 0.05, and the N-gain test results are 0.6913 medium criteria. This study concludes that interactive multimedia based on Problem-Based Learning was successfully developed, very feasible, and effective in improving the learning outcomes of the properties of light material for fifth-grade students of SDN Pesantren Semarang City.